(11+i)+(3-15i)=

Simple and best practice solution for (11+i)+(3-15i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (11+i)+(3-15i)= equation:


Simplifying
(11 + i) + (3 + -15i) = 0

Remove parenthesis around (11 + i)
11 + i + (3 + -15i) = 0

Remove parenthesis around (3 + -15i)
11 + i + 3 + -15i = 0

Reorder the terms:
11 + 3 + i + -15i = 0

Combine like terms: 11 + 3 = 14
14 + i + -15i = 0

Combine like terms: i + -15i = -14i
14 + -14i = 0

Solving
14 + -14i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + -14i = 0 + -14

Combine like terms: 14 + -14 = 0
0 + -14i = 0 + -14
-14i = 0 + -14

Combine like terms: 0 + -14 = -14
-14i = -14

Divide each side by '-14'.
i = 1

Simplifying
i = 1

See similar equations:

| (x^2+15)(x+30)=3000000 | | 6x(x-1)=7-25x | | (x^2+15)(x+30)=300 | | x^2=5(x+280) | | (-4+3i)-(-1+6i)= | | (2x^3+12)(x^2-15)=117 | | (2x^3+12)(x^2-15)=333 | | -4c(3+5)=32 | | (2x^3+12)(x^2-15)=2103 | | (2x^3+12)(x^2-15)=10 | | 9x^2=6x+3 | | (2x^3+12)(x^2-15)=0 | | (2x+4)-3x=-3(x+7) | | (3x+7y^5-5)(13y-7x^2)=3.14 | | t+(-2)=66 | | 4m=m+9 | | 33+(-7)=29+m | | -33+(-7)=29 | | 14y-4=3y | | 2x^2+(3x-5)=37 | | (3x^4+4x^3-5)-(8x^2-5x+8)= | | x-7y-14=0 | | x+2y=-13 | | 176=H+(219) | | (2x^2)=(3x^2-64) | | y=6x+b | | b=y-6x | | 2x+y=-14 | | 3+(4z+5)=31 | | 30x^2+27x= | | x/6-4=x/6 | | abs(2x-3)=4 |

Equations solver categories